2005
DOI: 10.1007/s00221-005-2366-y
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of conflict processing

Abstract: In this study we examined the neural correlates of conflict processing in the Stroop, counting, and digit-location tasks using event-related brain potentials (ERPs). The behavioral data revealed robust interference in response time and accuracy for all tasks. The interference effect for response time was greater in the Stroop task than the other tasks; in contrast, the interference effect for response accuracy was greater in the counting tasks than the other tasks. The N450 and sustained potential (SP) were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
172
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(211 citation statements)
references
References 38 publications
32
172
7
Order By: Relevance
“…Although the functional role of SP is less clear than that of FN, SP reflects a solution to a cognitive conflict [23] or response selection and goal maintenance, as a positive correlation is observed between response accuracy and SP amplitude [28]. However, in the present study, although individuals with schizotypal traits made more errors in response to incongruent stimuli than did the controls, the SP amplitudes did not differ between the two groups.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Although the functional role of SP is less clear than that of FN, SP reflects a solution to a cognitive conflict [23] or response selection and goal maintenance, as a positive correlation is observed between response accuracy and SP amplitude [28]. However, in the present study, although individuals with schizotypal traits made more errors in response to incongruent stimuli than did the controls, the SP amplitudes did not differ between the two groups.…”
Section: Discussioncontrasting
confidence: 78%
“…The functional role of SP is less clear than that of the FN. SP has been associated with conflict resolution [23] or response selection and goal maintenance [28]. The sources of SP are poorly understood, although the PFC has been considered as SP generator [25].…”
Section: Introductionmentioning
confidence: 99%
“…The observed correlations between these components and behavioral indices of interference and conflict adaptation argue for the functional relevance of the underlying neurocognitive mechanisms in conflict processing. The N400, in particular, seems to reflect functioning of a conflict-monitoring system (an increase in behavioral interference was associated with an increase in the N400 conflict score), which is presumably located in the dACC (Badzakova-Trajkov et al, 2009;Hanslmayr et al, 2008;Liotti et al, 2000;West, 2003;West, Jakubek, Wymbs, Perry, & Moore, 2005). Third, and probably most important, our results indicate that trait anxiety is linked to the way this system dynamically adjusts to changes in cognitive demands.…”
Section: N400mentioning
confidence: 60%
“…According to this view, inhibitory mechanisms engaged in the Stroop task most likely differed due to the difference in conflict strength from a common semantic representations rather than because L1 and L2 were supported by distinct representations (though it is not clear that ACC is activated by semantic conflict in the Stroop task; Chen et al 2011). An additional argument supporting that the stimuli in L1 and L2 actually differed in term of conflict strength comes from studies reporting that similar conflict processing are engaged across the various conflict tasks (Botvinick et al 2001;West 2003;West et al 2005; though see Banich et al 2000). For instance, West et al (2005) showed that the N450 conflict components manifesting in Stroop, counting and digit location tasks was related to a single latent variable, suggesting that a common brain network supported conflict processing in these three tasks.…”
Section: Discussionmentioning
confidence: 99%
“…An additional argument supporting that the stimuli in L1 and L2 actually differed in term of conflict strength comes from studies reporting that similar conflict processing are engaged across the various conflict tasks (Botvinick et al 2001;West 2003;West et al 2005; though see Banich et al 2000). For instance, West et al (2005) showed that the N450 conflict components manifesting in Stroop, counting and digit location tasks was related to a single latent variable, suggesting that a common brain network supported conflict processing in these three tasks. If similar mechanisms indeed support the processing of conflict at the latency of our interaction, our results unlikely follow from differences in the nature of the conflict induced by the word in L1 and L2.…”
Section: Discussionmentioning
confidence: 99%